Román állampolgárok Magyarországon - Kincses, Áron (Közép-Európai Közlemények, 2010)
The most considerable group of foreign population is the Romanian in Hungary. That’s why important to know what kind of features and spatial impacts characterize the international migration between these two neighbouring countries. In this article I am going to study the migration system from Romania to Hungary. From where and to where do Romanians move? This paper is devoted to the spatial characteristics of migration networks from Romania to Hungary. What kind of reasons may play a pivotal role in choosing a permanent address? Is the original Romanian location important? An analysis of the spatial distribution of migrants shows that there are two separate and considerable geographical motives, which mostly determine the location of foreigners in Hungary, namely, the effects of centres and the borders. The first case meant both a dynamics centre of immigration to Hungary and such emigration from Romania. There a wide variety of occupations can be found. I point out that highly educated and skilled workers have been attracted from a large distance to Budapest and Pest County. The second geographical motive is the proximity to the border, which is not a barrier, but rather a contact zone.